(untitled) (Global Journal of Human-Social Science, 2019)
Youths are said to be the future leaders of any country in the world Nigeria inclusive It is also a general belief that government all over the world try to invest strategically in her youth for them to be able to assume the position of leadership when the time comes In spite of this it appears that the training the investment of the Nigerian governments as well as the socialization of youth in Nigeria and Ondo State in particular seem to be inadequate because many of them instead of contributing meaningfully to the development of the society they are doing otherwise The Ondo State government in one of its spirited effort to combat this problem introduced the Skills Acquisition Programme to develop empower and engage the youth in the State This empirical study therefore assessed the level of impact this programme has on Youth empowerment and development in the State 27 copies of the questionnaire were administered on the trainers at the skill acquisition centers while 557 copies were given to the beneficiaries of the skills acquisition programme in Ondo State Thirteen members of the coordinating departments were chosen for an in-depth interview Findings revealed that the skills acquisition programme has been able to provide employment opportunities for youth beneficiaries reduce their involvement in social vices improved their standard of living